Evaluation of the Efficacy of Vancomycin-Soaked Autograft to Eliminate Staphylococcus aureus Contamination After Anterior Cruciate Ligament Reconstruction: Based on an Infected Rat Model. Issue 4 (March 2022) - Tong, Kai; Wei, Jian; Li, Zhenyu; Wang, Hui; Wen, Yinxian; Chen, Liaobin
Background: Vancomycin-soaked autograft application in anterior cruciate ligament reconstruction (ACLR) significantly reduces postoperative infection rates. However, the optimal vancomycin concentrations and time of vancomycin presoaking of autografts for preventing infection are still unknown. Purpose: To evaluate the efficacy of vancomycin-soaked autografts in preventing infection in rats with ACLR. Study Design: Controlled laboratory study. Methods: A total of 102 tendons of Wistar rats were harvested under sterile conditions from fresh cadaveric legs. Contamination with 2.0 × 10 4 colony forming units per milliliter of Staphylococcus aureus and soaking in different vancomycin concentrations for different soaking times was performed in vitro. In vivo, after being contaminated with S. aureus and soaked with optimal vancomycin solution treatment and sterile saline, the grafts were implanted in rat knees to finish ACLR surgery. At 2, 4, and 12 weeks after surgery, samples were harvested to observe signs of infection and tendon-bone incorporation via general postoperative conditions, serum inflammatory markers, microbiological counting, knee radiographs, micro–computed tomography, histologic staining, scanning electron microscopy, and biomechanical testing. Results: Bacterial contamination was eliminated when at least 5 or 10 mg/mL of vancomycin was applied for 30 minutes in vitro. Rats in the vancomycin-soaked graft group (5 mg/mL of vancomycin for 30 minutes) showed no significant signs of infection and fewer positive cultures than did those without presoaking. The vancomycin-soaked graft group had reduced serum inflammatory markers, tissue scores, inflammatory reactions in the joint tissue, and radiographic evidence of periarticular osseous destruction compared with the control group. At postoperative week 12, the vancomycin-soaked graft group showed good outcomes in tendon-bone incorporation via micro–computed tomography, histologic staining, and biomechanical testing. Conclusion: In a rat model of infection after ACLR, presoaking grafts in a 5-mg/mL vancomycin solution for 30 minutes could effectively prevent S. aureus contamination without affecting tendon-bone incorporation and knee function. Clinical Relevance: The present study could provide a specific solution for the use of vancomycin in the prevention of infection after ACLR clinically.